Knowledge and perception on lung cancer and its screening: a study among undergraduate students of the International Islamic University Malaysia, Kuantan Campus - Zainuddin, Norafiza; Thabit, Humairah (Advanced Medical and Dental Institute (AMDI), 2017)
Lung cancer is the second most common contributor to overall cancer–associated death in Malaysia after breast cancer. Many cases of late diagnosis are due to patient’s failure in recognizing the signs and symptoms of this disease. Objective: The aim of this research was to evaluate the knowledge on lung cancer and perception on its screening among IIUM Kuantan students. Method: This was a cross-sectional study whereby convenient sampling was used as the sampling method strategy. A total of 186 students participated, whereby majority was female students, single, and aged between 21 to 29 years old. Knowledge and perception scores were analyzed using descriptive statistics by denoting it in terms of frequency and percentages. Independent t-test, as well as one-way ANOVA, Mann-Whitney and Pearson correlation tests was used to find the association of gender, faculty, marital status, age and year of study (respectively) with knowledge and perception of students. Association between knowledge of lung cancer with perception of its screening was also evaluated using Pearson correlation test. Results: Most of IIUM Kuantan students portrayed good level of knowledge and perception. Socio-demographic factors that were significantly associated with students’ knowledge were age (p=0.001), year of study (p=<0.001) and faculty (p=<0.001). Whereas, only faculty was significantly associated with students’ perception (p=0.008). Besides, students’ level of knowledge was significantly associated with their perception (p=<0.001, r=0.326). Conclusion: Overall, the general knowledge of students regarding lung cancer and their perception towards lung cancer screening was good. Students with greater knowledge expressed better perception towards lung cancer screening.